Kegiatan Dakwah Sebagai Strategi Komunikasi Politik Islam Di Kota Palembang - ikhsan alqodrisyah; Bastian Bastian; Isna Wijayani; Desy Misnawati; Rahma Santhi Zinaida (Wardah, 2023)
A political party is an organization formed by a group of people who have the same goals and thoughts in achieving political goals. Indonesia is the largest Muslim country in the world, with 86.77% of the population being Muslim. There are many Islamic organizations that are developing in Indonesia, such as PPP, PKB, Muhammadiyyah, Nadhalatul Ulama and one of them is PKS which carries a religious, nationalist Islamic party and provides full support for people's aspirations. This party carries out the spread of Islam and da'wah methods engaged in politics. At this time, organizations that smell of Islam certainly have a negative stigma. Such as radicalism, terrorism and making hate speech against the organization. This type of research uses field research, namely conducting investigations of field symptoms and gathering sources to support research. Data collection techniques in this study used observation, interviews and documentation. The data used qualitatively. The results of this study indicate that the communication carried out by the PKS political party with the PKS DPD case study in Palembang City that using da'wah activities, persuasive communication, providing education to the community, makes Islamic parties at the forefront of people's aspirations, especially the middle to lower class, solid parties as well as prioritizing a sense of justice and prosperity for the people, especially for the future generation of leaders. The community's response strongly supports the work program of the PKS party and makes PKS a forum for people's aspirations as well as a da'wah method in spreading Islam.